Methods of corm disinfection in banana cultivars (Musa AAB) on their morphological and productive characteristics: Agroindustria - Avellán-Vásquez, Leonardo (2025)
The present research was carried out at the Experimental Farm Río Suma of the “Eloy Alfaro” Laica University of Manabí, Extension in El Carmen, with the aim of evaluating the level of damage caused by Cosmopolites sordidus Germar on two cultivars of Musa ssp. with different disinfection methods. For this purpose, six treatments were established resulting from the factorial combination of two banana varieties: V1 (Curare dwarf), V2 (Dominico Hartón) for factor A, and for factor B, the disinfection methods (MD): MD1 (chemical Cadusafos g·cormo-1), MD2 (physical immersion in hot water at 50ºC for 15 min), and MD3 (physical immersion in ambient water for 24 hours), arranged in a randomized complete block design with factorial arrangement of A (banana varieties) by B (disinfection methods of corms). Mean comparisons were performed using Tukey’s test at a 5% probability level. The evaluated variables were: corm damage (scale), plant height (m), pseudostem perimeter (cm), number of leaves, and bunch biomass (kg). The results showed statistically significant differences only at the variety level (P<0.05), with the Dominico Hartón cultivar being superior for the variables: corm damage, with 1.04 and 1.05 in phases IV and V, respectively, according to the Viladerbo scale; in the variable plant height (m) in all evaluated phases with: 2.98m (phase III); 3.48m (phase IV); and 3.96 m (phase V) and in the pseudostem perimeter only in phase V with 63.67 cm. Since there are no statistical differences between treatments (physical and chemical methods), it is suggested to use the former because it is more environmentally friendly, and it is also recommended to carry out future research with these treatments in several production cycles to minimize the use of agrochemicals.